Impact of diabetes mellitus on immunity to latent tuberculosis infection - Kumar, Nathella Pavan; Babu, Subash (Frontiers in Clinical Diabetes and Healthcare, 2023)
Tuberculosis (TB) is an infectious disease that poses a major health threat and is one of the leading causes of death worldwide. Following exposure to Mycobacterium tuberculosis (M.tb) bacilli, hosts who fail to clear M.tb end up in a state of latent tuberculosis infection (LTBI), in which the bacteria are contained but not eliminated. Type 2 diabetes mellitus (DM) is a noncommunicable disease that can weaken host immunity and lead to increased susceptibility to various infectious diseases. Despite numerous studies on the relationship between DM and active TB, data on the association between DM and LTBI remains limited. Immunological data suggest that LTBI in the presence of DM leads to an impaired production of protective cytokines and poly-functional T cell responses, accounting for a potential immunological mechanism that could leads to an increased risk of active TB. This review highlights the salient features of the immunological underpinnings influencing the interaction between TB and DM in humans.